Study of the effect of climate on free-living stages of Dictyocaulus filaria in Baghdad area. - AL-Samarrae, S. A.G.; Obaid, A. M. (The Iraqi Journal of Veterinary Medicine, 2000)
The survival ability and development of the free living stages of Dictyocaulus. filaria larvae were studied to understand the epidemiology of this parasite in irrigation system . Galvanised iron boxes were planted and containated at subsequent times by faeces containing the larvae. Then faecal , soil and pasture samples were examined weekly, climatic conditions were recorded in Baghdad area. The results showed that the free living larvae survived and migrated from the faeces to the soil and pasture in the squares of the 2 nd group of boxes which has been contaminated in January for a longer period in comparison with other groups. The larvae survived until the 1 st week of April in their faecal , soil and pasture samples. On the other hand , no larvae could be recovered after one week of contamination in the fifth group of boxes which has been contaminated in July. In the other groups of boxes, the larvae survived for (98) days in the 1 st group , (49) days in the 3 rd group and for (21) days in the 4 th group, however, the number of larvae in the soil and pasture in all groups was lower than that in the faeces, and the presence of larvae in the soil was recovered for short time The climatic condition during December , January , Febreuary and March had good influence on the survivability and moulting of the larvae in comparison with the adverse effect of other months . *Part of his M.Sc. Thesis.